Moderate mitral stenosis in pregnancy: the haemodynamic impact of diuresis. Issue 1 (16th December 2004) - Siva, A; Shah, A M
Abstract : A case of asymptomatic, newly diagnosed, moderate mitral stenosis in a 27 year old pregnant woman is described. A conservative management strategy with regular cardiac assessment was adopted and the patient remained well. Routine transthoracic echocardiography at 36 weeks' gestation showed the development of severe pulmonary hypertension with right ventricular pressure overload, which was successfully treated with oral diuretics resulting in rapid normalisation of pulmonary pressure. Mitral stenosis in pregnancy and its management in pregnancy are briefly discussed.